25 Line of therapy adjustment in a patient with advanced triple-negative breast cancer (TNBC) by using personalized ctDNA test for treatment response monitoring. (10th December 2020) - Azzi, Georges; Krinshpun, Shifra; Tin, Antony; Malashevich, Allyson; Malhotra, Meenakshi; Billings, Paul; Rodriguez, Angel; Aleshin, Alexey
Abstract : Background: Triple negative breast cancer (TNBC) is an aggressive form of breast cancer that is most difficult to treat due to the absence of hormone/growth factor receptors. 1 2 Metastatic TNBC (mTNBC) is particularly challenging, given the limited efficacy and duration of response to chemotherapy. 3 The repertoire of therapeutic options for mTNBC patients continues to increase with chemotherapeutic and immuno oncology based treatments and now includes sacituzumab govitecan, a novel antibody-chemotherapy conjugate. 4 Methods: Here we present a case study of a 40-year-old female who on biopsy of her left breast mass was diagnosed with TNBC. The patient underwent neoadjuvant chemotherapy with weekly administration of paclitaxel and carboplatin followed by dose-dense doxorubicin with cyclophosphamide. Following one-month, the patient underwent bilateral mastectomy, showing pathological staging ypT2 pN0. The patient underwent periodic radiological imaging along with the assessment of circulating tumor DNA in blood using a personalized and tumor-informed multiplex PCR, next-generation sequencing assay (Signatera bespoke, mPCR NGS assay) to identify the minimal residual disease (MRD) and treatment response. Results: After surgery, MRD assessment revealed ctDNA positive status (0.41 MTM/mL) prompting PET/CT scan that revealed liver metastasis. Continued ctDNA monitoring showed continuous increase in ctDNA concentration (287.09 MTM/mL). Separate analyses indicated MSI-high and PD-L1 positive tumor status, leading to the initiation of the first line of therapy (nab-paclitaxel and Atezolizumab), which resulted in ctDNA decline (39.62 MTM/ml). Weekly ctDNA monitoring noted a rapid increase a month later (178 MTM/ml to 833.69 MTM/ml) within a 2-week interval, which corresponded to disease progression on imaging. Given non-responsiveness with the first-line therapy, the patient was initiated with sacituzumab govitecan. Following this, a rapid decline in the ctDNA level was observed within a week (364.07 MTM/mL) with a downward trend to 73.03 MTM/ml by two weeks. An interval PET/CT scan showed a mixed response. Continued monitoring of ctDNA demonstrated ctDNA levels <5MTM/mL for a period of two months before serially rising again (to 89.27 MTM/ml). PET-CT ordered in response to increasing ctDNA levels confirmed progression involving hepatic and lung lesions. A new line of therapy with nivolumab and ipilimumab was subsequently initiated. Conclusions: Serial monitoring of ctDNA enables early detection of therapy resistance and provides a rationale for treatment change/optimization/discontinuation as compared to periodic imaging that is currently the standard of care. The ease and convenience of using ctDNA-based testing as frequently as every week clearly identified earlier non-responsiveness to IO and also identified earlier acquired resistance to antibody-drug conjugate, enabling a prompt switch to alternative therapy. Ethics Approval: N/A Consent: N/A References: Anders C, Carey LA. Understanding and treating triple-negative breast cancer. Oncology (Williston Park) . 2008;22(11):1233–1243. Mehanna J, Haddad FG, Eid R, Lambertini M, Kourie HR. Triple-negative breast cancer: current perspective on the evolving therapeutic landscape. Int J Womens Health 2019;11 :431–437. Published 2019 Jul 31. doi:10.2147/IJWH.S178349 Treatment of Triple-negative Breast Cancer. American Cancer Society Website. Updated 2020. Accessed August 10, 2020. https://www.cancer.org/cancer/breast-cancer/treatment/treatment-of-triple-negative.html Bardia A, Mayer IA, Vahdat LT, et al. Sacituzumab govitecan-hziy in refractory metastatic triple-negative breast cancer. N Engl J Med 2019;380(8):741–751. doi:10.1056/NEJMoa1814213